Stakeholders Consultation on the National Fisheries Fisheries and Aquaculture Policy (2024-2028) - Ragasa, Catherine; Onoja, Anthony; Siriwardena, Sunil; Ansa, Ebinimi; Popoola, Olufemi (WorldFish, 2023)
This report summarizes the processes of developing the national fisheries and aquaculture policy in Nigeria in a 2-day consultation workshop with more than 63 stakeholders from the government ministries, nongovernmental and civil society organizations, research institutes, universities, and donors.